Cardiovascular screening of elite athletes by sporting organizations in Australia: A survey of chief medical officers - Orchard, J. J.; Orchard, J. W.; Toresdahl, B.; Asif, I. M.; Hughes, D.; La Gerche, A.; Semsarian, C. (Clinical Journal of Sport Medicine, 2021)
Objective: To compare cardiovascular screening policies of Australian elite sporting organizations.